2006
DOI: 10.1007/s11414-006-9038-y
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes About Stimulant Medication for Attention-Deficit/Hyperactivity Disorder Among African American Families in an Inner City Community

Abstract: Limited information exists on views among African American families living in low-income, inner-city communities regarding the treatment of children with attention-deficit/hyperactivity disorder (ADHD). Parents of children treated for ADHD in an urban primary care setting were recruited to complete a survey to assess attitudes toward stimulant medications. Although most (71%) were initially hesitant to use stimulants based on what they heard in the lay press, 63% would recommend stimulant medication to a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…First, engagement with behavioral health care is often problematic. [10][11][12][13][14] Second, low-income parents, particularly those of inattentive or hyperactive/impulsive children, have an increased prevalence of depression and adult ADHD, 15 which have been associated with poorer child symptom trajectories. 16,17 Third, behavioral comorbidities, particularly oppositionality, are highly prevalent among low-income populations, and can limit the effectiveness of strategies designed to address core ADHD symptoms.…”
Section: Articlementioning
confidence: 99%
“…First, engagement with behavioral health care is often problematic. [10][11][12][13][14] Second, low-income parents, particularly those of inattentive or hyperactive/impulsive children, have an increased prevalence of depression and adult ADHD, 15 which have been associated with poorer child symptom trajectories. 16,17 Third, behavioral comorbidities, particularly oppositionality, are highly prevalent among low-income populations, and can limit the effectiveness of strategies designed to address core ADHD symptoms.…”
Section: Articlementioning
confidence: 99%
“…Our analysis of parent comments corroborates previous work in this area and provides a far more comprehensive collection of factors than previous studies. [4][5][6][7][23][24][25][26][27][28][29][30][31][32][33][34][35] Previous efforts implementing the American Academy of Pediatrics clinical practice guidelines for the diagnosis and treatment of ADHD demonstrated a need to augment the time-constrained efforts of physicians to educate and support parents. 36 Future studies are needed to develop and test systems to support parents facing treatment decisions for their child newly diagnosed with ADHD.…”
Section: Table 4 Domain 3: Continued Doubt and Uncertaintymentioning
confidence: 99%
“…On the one hand, prior research has shown that very few parents believe prescription medication leads to drug abuse, and 70% feel that medication improves adult outcomes in the longterm (dosReis et al, 2006;dosReis et al, 2003). Moreover, most families believe that medication can help children (Olaniyan et al, 2007) and is safe if recommended by a physician (dosReis et al, 2006;dosReis et al, 2003). On the other hand, some parents feel that too many children are medicated (dosReis et al, 2006;dosReis et al, 2003;Pescosolido, Perry, Martin, McLeod, & Jensen, 2007).…”
Section: Introductionmentioning
confidence: 99%